(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
To calculate the water temperature of the White Sea we used two models of large-scale hydro-and thermal dynamics, maintained by the authors. Comparing two models, we show that the first one describes summer hydrophysical conditions better, while the second model is better for winter conditions. Now we are trying to improve and combine two models in order to describe the state of the Sea more accurately.